2004
DOI: 10.1016/j.ajog.2004.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Placental corticotropin-releasing hormone (CRH), spontaneous preterm birth, and fetal growth restriction: A prospective investigation

Abstract: For deliveries occurring after 33 weeks' gestation (the time of CRH sampling in this study), our findings support the notion that in humans placental CRH may play an impending, direct role in not only the physiology of parturition but also in processes related to fetal growth and maturation. Our results also support the notion that the timing of onset of parturition may be determined or influenced by events occurring earlier in gestation rather than those close to the time of actual onset of labor (ie, the not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
255
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 344 publications
(277 citation statements)
references
References 36 publications
14
255
0
4
Order By: Relevance
“…The second possibility is that under stressful conditions, the fetus must compete with its host (the mother) for resources required for coping and survival (Stearns, 2005). This possibility is consistent with findings indicating that fetal exposure to stress hormones and synthetic corticosteroid administration are associated with fetal growth restriction (Bloom et al, 2001;French et al, 1999;Reinisch et al, 1978;Wadhwa et al, 2004). The purposes of the present study were to (1) test these competing hypotheses by evaluating the consequences of exposure to stress hormones during pregnancy for physical and neuromuscular development in infants and (2) determine the specific periods during pregnancy during which stress hormones influence newborn physical and neuromuscular maturation.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…The second possibility is that under stressful conditions, the fetus must compete with its host (the mother) for resources required for coping and survival (Stearns, 2005). This possibility is consistent with findings indicating that fetal exposure to stress hormones and synthetic corticosteroid administration are associated with fetal growth restriction (Bloom et al, 2001;French et al, 1999;Reinisch et al, 1978;Wadhwa et al, 2004). The purposes of the present study were to (1) test these competing hypotheses by evaluating the consequences of exposure to stress hormones during pregnancy for physical and neuromuscular development in infants and (2) determine the specific periods during pregnancy during which stress hormones influence newborn physical and neuromuscular maturation.…”
Section: Introductionsupporting
confidence: 75%
“…Despite the necessity of cortisol for fetal maturation, it has been repeatedly demonstrated that women receiving synthetic corticosteroids (administration commencing typically around the 24th week gestation) were more likely to deliver infants with fetal growth restriction and low birth weight, even when controlling for length of gestation, suggesting that high levels of glucocorticoids may be detrimental to fetal growth (Bloom, Sheffield, McIntire, & Leveno, 2001;French, Hagan, Evans, Godfrey, & Newnham, 1999;Reinisch, Simon, Karow, & Gandelman, 1978). Similarly, exposure to CRH at 33 weeks' gestation has been associated with fetal growth restriction (Wadhwa et al, 2004). Nevertheless, no study has examined whether the timing of prenatal exposure to stress hormones affects fetal growth and maturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Other studies have found associations between stress hormones (i.e., cortisol and adrenocorticotrophin-releasing hormone) and PTB, though IPV as a stressor was not specifically measured. [43][44][45] These findings highlight the need for further research on the neuroendocrine changes evident in pregnant women experiencing IPV. An enhanced understanding of the links between violence, HPA activation, utero-placental perfusion, and adverse neonatal outcomes may provide an important pathway to reducing disparities in neonatal outcomes.…”
Section: Severity Of Violence and Adverse Neonatal Outcomesmentioning
confidence: 99%
“…Obstetric risk was defined as the presence of medical complications in the index pregnancy. Risk conditions were ascertained by extensive medical chart review and coded as a binary variable as previously described (82). The study population was predominantly (72%) at low risk with respect to adverse birth outcomes.…”
Section: Methodsmentioning
confidence: 99%